Analisis Kinerja Operasional Dan Pelayanan Bus AKAP (Studi Kasus PO. Haryanto Kelas Executive Trayek Jepara – Jakarta) - Syahputra, M Reza; Hariani, Mira Lestira; Sugiyanto, Martinus Agus; Farhan, Ohan; Novriani, Shinta (Jurnal Civil Engineering Study, 2023)
PO. Haryanto is an Otobus company from Kudus, Central Java, which is engaged in Inter-City Inter-Provincial (AKAP) bus transportation services, one of which operates from Jepara to Jakarta with the type of service Executive Class. This study aims to determine the performance and tariffs based on vehicle operating costs. In this study, data was collected through observation, interviews and questionnaires directed to service users. The method for analyzing operational performance, calculating tariffs and operating costs for vehicles refers to the method of the Ministry of Transportation SK.687/AJ.206/DRJD/2002, and analysis of service performance using the method of Importance Performance Analysis (IPA). Results of operational performance in terms of load factor obtained by 70,79%, the value of travel speed is 53,70 km/hour, the frequency of service is obtained 4 vehicles/hour, the service time is obtained 2 hours (morning and evening), the travel time is 1,14 minutes/km, the number of fleets operating 100%, and circulation time of 34,05 hours. The actual fare for the PO. Haryanto bus for the Jepara – Jakarta route is IDR 240.000. The results of the tariff analysis based on the BOK with the furthest distance traveled obtained a BOK value of IDR 4.803.356,79 with a tariff value of IDR 251.604,40. PO. Haryanto bus service performance results with the method IPA shows some performance indicatorsa that should be maintained and some that should be improved.